TYPES OF BILINGUAL EDUCATION PROGRAM - Ima H, Dwi (Lingua Scientia, 2013)
Abstract: Although the international school program has been cancelled by the government of Indonesia, it seems that the societyâs need of an international standard school is still emerging. It can be shown from the enthusiasm of studentsâ parents to urge their children to enroll to international standard school set up by private institution. This paper is intended to give insights on the discussion about conceptualization of bilingual education; sets of goals of bilingual education.Â Â  This discussion is provided with a wideÂ  range of research studies on several issues related to bilingual programs which have been conducted in several places, for instance, studies on what benefits the students will get through bilingual education or on the way around what disadvantages will the students face with the implementation of bilingual program, teacher or student perception on bilingual instruction, strategies of teaching and learning through two languages, the effects of bilingual education on the student academic achievement and some more other prominent studies.